PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO DAN RETURN ON ASSETS PADA HARGA SAHAM - Suryawan, I Dewa Gede; Wirajaya, I Gde Ary (E-Jurnal Akuntansi, 2017)
In today's era, many countries pay attention to the capital market because it has an important role as a strengthening of economic resilience of a country. Capital Market (capital market) is a meeting between parties who have excess funds with parties who need funds by way of trading securities. Stock price is a very important factor for capital market players, because the fluctuation of stock price will affect the profit of investors and corporate image. If the stock price increases then investors will get a good profit from the difference in stock price increase and dividends to be received. An increase in stock prices will also make the company more likely to get capital because of a good image in the eyes of investors. The purpose of this research is to provide empirical evidence about the influence of Current ratio, Debt to equity ratio and Return on asset at Stock Price. This study was conducted on companies that have been incorporated in the LQ-45 Index during the period 2013-2015. The number of samples taken as many as 55 companies, using saturated sample technique. Data collection was done through non participant observation method with secondary data. The analysis technique used is multiple linear regression analysis. Based on the results of the analysis found that the variable Current ratio and Debt to equity ratio does not affect the stock price while the variable Return on assets have a positive effect on stock prices.